The Effect of Digital Marketing Strategy, Brand Awareness, and Customer Satisfaction on Shopee Customer Loyalty in Batam with Customer Engagement as a Mediator - Warni Sarawasti Silitonga; Bambang Budhijana; Batara Maju Simatupang; Antyo Pracoyo (Publikasi Indonesia, 2026)
The rapid development of digital technology has transformed marketing strategies in Indonesia, especially in e-commerce. Shopee, as a leading e-commerce platform, employs digital marketing strategies to attract consumers and maintain their loyalty. However, to stay competitive, it is crucial to understand the factors influencing customer loyalty, such as brand awareness, customer satisfaction, and customer engagement. Analyze the impact of digital marketing strategies, brand awareness, and customer satisfaction on Shopee's customer loyalty. Examine the role of customer engagement as a mediating variable in these relationships. This study uses a quantitative approach with a causal design. The sample consists of 200 active Shopee users in Batam. Data was collected using a six-point Likert scale questionnaire and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS-SEM). The results indicate that digital marketing strategies, brand awareness, and customer satisfaction positively influence customer loyalty and customer engagement. Customer engagement serves as a partial mediator in the relationship between these three variables and customer loyalty. The study concludes that factors like digital marketing strategies, brand awareness, and customer satisfaction influence customer loyalty, with customer engagement acting as a mediator that strengthens these effects.